The influence of Green Human Resources Management (GHRM) practices on Environmental Management System (EMS) performance at Pasir Gudang Industrial Estate / Nur Syuhada Ahmad Faridi - Ahmad Faridi, Nur Syuhada (Faculty of Business and Management, 2018)
The main purpose of this study is to identify the influence of Green Human Resource Management (GHRM) practices on Environmental Management System (EMS) performance at Pasir Gudang Industrial Estate. The objective of this study to identify, assess, examine and analyze the 5 practices of GHRM towards EMS, such practices are Top management commitment, Employee Environmental Communication, Employee Environmental Training, Employee Environmental Rewards and Employee Environmental Involvement. A sample of 104 respondents were selected through judgment and convenience sampling. The study is conducting in manufacturing companies at Pasir Gudang Industrial Estate and study focus to HR department people or top management persons to contribute in answering the survey. SPSS program was used in this research paper in order to analyze the data gathered such as regression analysis, Peason’s Coefficient, analyze the reliability of questionnaires and so on. This research study was explored the five of GHRM practices, these are Top Management Commitment, Employee Environmental Communication, Employee Environmental Training, Employee Environmental Reward and Employee Environmental Involvement. The questionnaires for all variables were adapted from the previous researchers and the language of questionnaires are all in English. At the of studied, researcher points out some of research limitations and develops some of recommendations for organizations at Pasir Gudang Industrial Estate regarding to GHRM practices and for future research.